2010
DOI: 10.1002/art.27271
|View full text |Cite
|
Sign up to set email alerts
|

Tumor necrosis factor neutralization results in disseminated disease in acute and latent Mycobacterium tuberculosis infection with normal granuloma structure in a cynomolgus macaque model

Abstract: Objective. An increased risk of tuberculosis has been documented in humans treated with tumor necrosis factor ␣ (TNF␣)-neutralizing agents. In murine models, impaired signaling by TNF causes exacerbation of both acute and chronic infection associated with aberrant granuloma formation and maintenance. This study was undertaken to investigate immune modulation in the setting of TNF neutralization in primary and latent tuberculosis in a non-human primate model.Methods. Cynomolgus macaques 4 years of age or older … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
212
0
3

Year Published

2010
2010
2014
2014

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 209 publications
(233 citation statements)
references
References 39 publications
14
212
0
3
Order By: Relevance
“…Extrapulmonary manifestation was higher in patients receiving anti-TNF-a therapy than in the general population, which has also been shown in previous studies [6,9,10]. These findings may be explained by systemic spreading of mycobacteria due to inhibition of TNF-a by anti-TNF-a therapy in TB patients [28,29].…”
Section: Discussionsupporting
confidence: 83%
“…Extrapulmonary manifestation was higher in patients receiving anti-TNF-a therapy than in the general population, which has also been shown in previous studies [6,9,10]. These findings may be explained by systemic spreading of mycobacteria due to inhibition of TNF-a by anti-TNF-a therapy in TB patients [28,29].…”
Section: Discussionsupporting
confidence: 83%
“…Bacterial numbers were very low in both groups of treated animals after prophylactic treatment. Although bacterial numbers were also low in the latent (untreated) group, 80% of untreated animals in this study reactivated the infection after TNF neutralization, similar to our previously reported data (22). Thus, short-term drug treatment reduced bacterial load or altered granuloma structure and prevented reactivation, even without sterilizing all of the animals.…”
Section: Ifn-γ Responses In the Airways During Treatment Do Not Predictsupporting
confidence: 90%
“…In macaques, bacterial numbers are generally quite low during latent infection and only increase upon reactivation (19,22). Thus, we assumed that simply comparing bacterial numbers in latent monkeys with and without drug treatment would not provide sufficient sensitivity for identifying an efficacious drug against bacilli present in latent animals.…”
Section: Short-course Mtz or Inh/rif Is As Effective As 6 Mo Inh In Pmentioning
confidence: 99%
See 1 more Smart Citation
“…TNF knockout mice -TNF is an important mediator in both innate and adaptive immunity and plays a pivotal role in inflammatory phenomena that culminate in either pathogenesis or resistance in mycobacterial disease (Adams et al 1995, Flynn et al 1995, Bean et al 1999, Kaneko et al 1999, Lin et al 2010). Recently, the association of SNP TNF-308A with protection against leprosy was confirmed (Cardoso et al 2011a).…”
Section: Interleukin (Il)-12/il-23/interferon (Ifn)γ Axis -mentioning
confidence: 99%